New Fossil Scorpion from the Chiapas Amber Lagerstätte - Riquelme, Francisco (PLoS One, 2015)
A new species of scorpion is described based on a rare entire adult male preserved in a cloudy amber from Miocene rocks in the Chiapas Highlands, south of Mexico. The amber-bearing beds in Chiapas constitute a Conservation Lagerstätte with outstanding organic preservation inside plant resin. The new species is diagnosed as having putative characters that largely correspond with the genus Tityus Koch, 1836 (Scorpiones, Buthidae). Accordingly, it is now referred to as Tityus apozonalli sp. nov. Its previously unclear phylogenetic relationship among fossil taxa of the family Buthidae from both Dominican and Mexican amber is also examined herein. Preliminarily results indicate a basal condition of T. apozonalli regarding to Tityus geratus Santiago-Blay and Poinar, 1988, Tityus (Brazilotityus) hartkorni Lourenço, 2009, and Tityus azari Lourenço, 2013 from Dominican amber, as was Tityus (Brazilotityus) knodeli Lourenço, 2014 from Mexican amber. Its close relationships with extant Neotropic Tityus-like subclades such as ‘Tityus clathratus’ and the subgenus Tityus (Archaeotityus) are also discussed. This new taxon adds to the knowledge of New World scorpions from the Miocene that are rarely found trapped in amber.